Sistem Monitoring Kadar Gas Berbahaya Di Lingkungan Industri Menggunakan Protokol MQTT - Sunu Dias Widhi Kurniadi; Mochammad Hannats Hanafi Ichsan; Gembong Edhi Setyawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Air is an important factor in life, but with the increasing physical development of cities and industrial centers, air quality has changed. With today's rapid development, particularly in the industrial and technological sectors, it increases the disruption to air quality due to emissions from the fuel combustion process. Based on these problems, a system of monitoring of hazardous gas content present in the industrial environment uses MQTT protocol and uses ESP8266. In this system the MQ-7 and MQ-135 sensors aim to detect the intensity of changes of carbon monoxide and nitrogen oxide gas levels and then processed by the Arduino microcontroller until the results of the data will be sent to the Thingsboard to be displayed. The execution time required by the system for data processing is 1.3 seconds and the delivery time to the web averages 1,879 seconds.